2020
DOI: 10.1055/a-1147-4671
|View full text |Cite
|
Sign up to set email alerts
|

Anti-biofilm and Virulence Factor-Reducing Activities of Essential Oils and Oil Components as a Possible Option for Bacterial Infection Control

Abstract: Pathogenic biofilm-associated bacteria that adhere to biological or nonbiological surfaces are a big challenge to the healthcare and food industries. Antibiotics or disinfectants often fail in an attempt to eliminate biofilms from those surfaces. Based on selected experimental research, this review deals with the potential biofilm-inhibiting, virulence factor-reducing, and biofilm-eradicating activities of essential oils and single essential oil compounds using Staphylococcus aureus, Escherichia coli, Pseudomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 103 publications
(155 reference statements)
4
34
0
3
Order By: Relevance
“…Concerning the motility controlled by QS, in concordance with our results, hydroalcoholic extracts (96% ethanol) from Citrus peels, including C. limon , C. medica and C. aurantium , reduced Campylobacter jejuni swarm motility (35–59%) [ 32 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Concerning the motility controlled by QS, in concordance with our results, hydroalcoholic extracts (96% ethanol) from Citrus peels, including C. limon , C. medica and C. aurantium , reduced Campylobacter jejuni swarm motility (35–59%) [ 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…Besides biofilm, extracellular virulence factors secretion also plays a vital role in the effective pathogenesis of P. aeruginosa . It was previously reported that some essential oils could interfere with the QS system regulation and the formation of virulence factors [ 31 , 32 ]. In line with this, the autoinducer production decreased between 26 and 55% in the lemon essential oils assayed; this result is similar to that found in grapefruit and mandarin essential oils [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…on microbes such as bacteria or fungi [25]. It can therefore be assumed that this also applies to their antiviral activity.…”
Section: Discussionmentioning
confidence: 99%
“…2) and their oxygenated derivatives (alcohols, aldehydes, esters, ketones, phenols, and oxides) [13,[23][24][25]. Numerous in vitro and in vivo studies have shown that EOs and many of their individual EOCs exhibit different biological properties, for example, antibacterial [13,23,25], antifungal [13], antiviral [13], antioxidant [26,27], immunomodulatory [28,29], anti-inflammatory [24,27], and wound healing effects [30]. Due to their fat solubility, low molecular weight, and small size, the EOCs are able to pass through the skin, mucosa, and cell membranes and thus enter the systemic body circulation [13,24].…”
Section: Chemical Characteristics and Biological Effects Of Essential Oilsmentioning
confidence: 99%
“…Ref. [ 8 , 9 ]), a quick search for biofilm or anti-biofilm products online, results in a long list of very questionable products that make outrageous claims. It would be a pity if the commercial biofilm arena were overtaken by these types of products, which would likely sour the public image of the biofilm problem and result in a downward trend in funding over the long-term.…”
Section: Industrymentioning
confidence: 99%